Padrões evolutivos associados a especialização ecológica em flores em diferentes grupos de espécies de Drosophila - Carvalho, Tuane Letícia (2023)
At the interface between ecological, genetic and evolutionary processes, it is of particular interest to understand the molecular changes that have allowed biological diversification and adaptation to different niches. Drosophilidae comprises a highly diverse taxon of the order Diptera, with species exhibiting distinct patterns of geographic distribution and ecological specialization. As such, these species provide a unique opportunity to assess important evolutionary factors that have shaped biological diversity, and to link genetic patterns to ecological processes. This is particularly noteworthy when considering species of neotropical drosophilids that use flowers during all their cycle, known as anthophiles species. Among these, the species of the genus Drosophila belonging to the groups bromeliae and flavopilosa of the subgenus Siphlodora or to the group lutzii of the subgenus Drosophila are particularly representative. One of the peculiarities of these groups is the presence of species with different degrees of ecological specialization, ranging from species with specialist habits to more generalist species. This important feature makes these species potential models for understanding the scenario and patterns of molecular evolution associated with the diversification of antophilous species. In this sense, in this thesis, we sought to evaluate patterns and processes of molecular evolution potentially associated with the ecological diversification of these species. In the first chapter, we provide important insights into the evolutionary processes involved in the diversification of the lutzii species complex. In the second chapter, our results show that similar ecological pressures and evolutionary histories have driven the diversification of transposition elements in anthophilous species. Furthermore, we show that opportunities for horizontal transfer are facilitated by overlapping abiotic niches. Finally, in the third and last chapter, we highlight the adaptive role of the Cyp450 gene family, related to metabolism and detoxification, in the evolution of anthophilous species and other species from different lineages of Drosophilidae. Through these studies, we were able to demonstrate the impact of ecological diversification at different scales, both in terms of molecular evolution and speciation.